Thrombotic Thrombocytopenic Purpura: A Case Presenting with Acute Ischemic Colitis - Joseph R. H. See; Tarek Sabagh; Christopher J. Barde (Case Reports in Hematology)
Thrombotic thrombocytopenic purpura (TTP) consists of the pentad of thrombocytopenia, hemolytic anemia, fever, neurologic abnormalities, and renal disease. We present a case report of acute TTP following a bout of ischemic colitis. This report reminds the clinician that ischemic colitis can be an atypical presentation of TTP. The prompt recognition and treatment of this disease process resulted in a good prognosis for our patient.